Travellux Iron Machine / Liana Mohd Zulkamal - Mohd Zulkamal, Liana (2020)
LMZ Sdn. Bhd. produce this Travellux iron machine is due to some reasons. Some of the objectives are to produce product that more convenient such as portable which can be folded into smaller size and can be bring to everywhere, to increase differentiation product as provided it in various colours and to produce product that used high technology but still affordable for the users. Our company targets are from small to large scale of customers especially for travellers, women workers, and undergraduate students. Travellux will give profitability as people nowadays more preferred in product that simple but can save more of their times times. However, there are still some problems occur in the process of Travellux production. Some of the problems are one and only competitor, Effie, is basically a well-known brand as they are the first one that invented iron machine in the world, company is still new in this field, thus they rely the most with external sources such as loans from the bank and Travellux used high technology in its production, thus company needs to find technical workers that have the appropriate skills and qualifications that in line with the requirement. In Malaysia, we only have a few workers that fulfilled all the requirements.